Body and Head Morphometric of Kacang Goat under Semi Intensive Management at Fishpond Area in Sidoarjo Regency, Indonesia - Inggita Leli Murtika; Desinta Wulandari; Fitria Ella Wardani; Ahmad Furqon; Wike Andre Septian; Tri Eko Susilorini; Suyadi Suyadi (ANIMAL PRODUCTION, 2022)
Morphometric characterization is the basis of conservation strategies, performance improvement, breeding, and sustainable utilization plan. The purpose of this research was to determine the morphometrics of the Kacang Goats at the fishpond area in Sidoarjo Regency based on different ages and sex. The fishpond area in Sidoarjo is a closed area where goats are raised and have the potential for inbreeding with the consequence of smaller-sized offspring than normal. Morphometric measurements included the head, ears, neck, body, legs, tail, and horns. This research used a descriptive analysis approach, presenting data in form of mean, standard deviation, and coefficient of variation. The result showed that the average face length of male vs. female Kacang goats was 16.73 ± 2.40 cm vs. 19.68 ± 2.44 cm; with a face width of 11.25 ± 2.91 cm vs. 19.52 ± 3.18 cm; ear length of 14.62 ± 1.38 cm vs. 16.46 ± 1.47 cm; neck length of 15.53 ± 2.65 cm vs. 15.35 ± 2.14 cm; horn length of 7.41 ± 4.10 cm vs. 6.59 ± 2.89 cm; chest circumference of 59.33 ± 8.18 cm vs. 67.80 ± 6.32 cm; body length of 51.45 ± 6.70 cm vs. 56.91 ± 6.54 cm; body height of 54.41 ± 7.22 cm vs. 62.01 ± 5.53 cm; tail length of 13.21 ± 2.01 cm vs. 14.77 ± 3.37 cm; hind leg length of 39.20 ± 5.26 cm vs. 47.74 ± 5.47 cm; and front leg length of 37.00 ± 8.84 cm vs. 44.63 ± 8.65 cm. This research concludes that Kacang Goats in Sidoarjo has characteristics according to SNI standard, and the morphometric size was larger in female than male goats.